2015
DOI: 10.4103/0974-8520.175553
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of Apamarga Kshara Yoga in the management of Shvitra (vitiligo)

Abstract: Introduction:Vitiligo is a progressive, idiopathic, pigmentation disorder of the skin, characterized by hypopigmented patches. This condition is compared with Shvitra in Ayurveda. Many Ayurvedic drugs are beneficial in such cases and Apamarga Kshara Yoga is one among them.Aim:To evaluate the efficacy of Apamarga Kshara Yoga in Lepa and ointment forms in the management of Shvitra.Materials and Methods:Total 50 patients of Shvitra were randomly grouped into two. Patients registered in Group A (n = 25) were treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Acharya Charaka also stated that psychological factors may induce stress in the patients and become the triggering factor that triggers the disease manifestation mechanism. [ 18 ] 68.35% of patients had sour taste dominancy followed by sweet taste (55.69%) and salty taste (45.56%) in their diet. It revealed that Madhura (sweet), Amla (sour), and Lavana (salty) Rasa causes aggravation of Kaphadosha , Amla Rasa (sour taste) causes Rakta Dushti .…”
Section: Discussionmentioning
confidence: 99%
“…Acharya Charaka also stated that psychological factors may induce stress in the patients and become the triggering factor that triggers the disease manifestation mechanism. [ 18 ] 68.35% of patients had sour taste dominancy followed by sweet taste (55.69%) and salty taste (45.56%) in their diet. It revealed that Madhura (sweet), Amla (sour), and Lavana (salty) Rasa causes aggravation of Kaphadosha , Amla Rasa (sour taste) causes Rakta Dushti .…”
Section: Discussionmentioning
confidence: 99%
“…Local application of ghee and Dashanga Lepa along with Kaishore Guggulu and Sanjivani Vati in a case study demonstrated healing of dry gangrene [ 107 ]. Ghee, honey along with Apamarga Kshara Yoga Lepa was found to be effective in treatment of Vitiligo ( shvitra ) [ 108 ]. Ghee along with Guduchi and Bhringaraja powder showed promising results in treatment of Eczema [ 109 ].…”
Section: Review Of Modern Literature On Ghee In Context Of the 15 Ben...mentioning
confidence: 99%